The ME-BYO index: A development and validation project of a novel comprehensive health index - Nakamura, Sho; Watanabe, Ryo; Saito, Yoshinobu; Watanabe, Kaname; Chung, Ung-il; Narimatsu, Hiroto (Frontiers in Public Health, 2023)
Quantifying health status and identifying modifiable factors are essential for effective and individualized prevention of age-related conditions and for promoting health during aging. The ME-BYO concept from Kanagawa Prefecture, one of Japan’s largest prefectures, can be used to establish a healthy aging society. In disease etiology, ME-BYO considers the status of an individual’s body and mind as changing continuously from healthy to sick instead of being a dichotomy between the two. ME-BYO conceptualizes the entire process of this change. The ME-BYO index was developed in 2019 to comprehensively and numerically measure and visualize an individual’s current health status and future disease risk by quantifying data on the four domains of metabolic function, locomotor function, cognitive function, and mental resilience. The ME-BYO index has been implemented in the personal health management application “My ME-BYO.” However, scientific validation of this index and the development of a practical application using healthcare data remain to be completed. In 2020, our research team started a project to refine the ME-BYO index using data from the Kanagawa ME-BYO prospective cohort study, which is a large population-based genomic cohort study. This project will scientifically evaluate the ME-BYO index and develop a practical application for promoting healthy aging.